Hubungan Kepatuhan Prosedur Tetap Perawatan Ulkus Diabetikum dengan Kepuasan Pasien Diabtes Melitus Pengguna BPJS PBI di RSUD Sleman - Widuri Widuri (LPPM STIKES Guna Bangsa Yogyakarta, 2016)
Background: Satisfaction is the degree of one's feelings after comparing the performance or results which felt with expectations. In this case the patient satisfaction as a benchmark the quality of Sleman hospital where the vision and mission is a quality health service delivery. Especially for compliance using SOP, the Sleman hospital is part of the process of achieving Satisfaction Patient Diabetes Mellitus User BPJS PBI at Sleman Hospital.